WOMEN ON THE MOVE (Sociología y tecnociencia, 2013)
The special issue Women on the Move that the reader holds in their hands is the result of the hard work of very creative specialists in gender and mobility. Research on mobility and gender has progressively advanced from traditional, non-gender-specific literature on migration or mobility of highly skilled people. And, as these authors prove, the topic is already quantitatively and qualitatively relevant.